Penerapan Communication Skill Training pada Pelaksanaan Psikoedukasi Keluarga yang Merawat Klien dengan Hipertensi - Hari Widiyatmini; Herni Susanti; Ria Utami Panjaitan; Yossie Susanti Eka Putri; Giur Hargiana (Journal of Telenursing (JOTING), 2023)
This research aims to provide an overview of the application of communication skills training in implementing psychoeducation for families caring for clients with hypertension. The research method used in this research is a case report that describes and analyzes the benefits of implementing communication methods with families in caring for clients with hypertension. The study showed a change in healthy lifestyle and an increase in the quality of care for clients with hypertension after implementing communication skills training in the implementation of family psychoeducation. In conclusion, applying communication skills training in the performance of psychoeducation for families caring for clients with hypertension can improve healthy lifestyles and the quality of health care services for clients with hypertension. Keywords:Hypertension, Communication Skills, Therapeutic Communication, Psychoeducation